Memahami Kembali Nasionalisme Indonesia - Bambang Purwanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
Nationalism is a given cultural reality which keeps changing its meaning through out our history. Such changing is partly due to a manipulative exercise by the rulers, partly through socialization of the so called 'national history'. Societal conflict and tention emerged in many part of Indonesia recently has been due to unfinished transformations, yet pursuing the manipulative path of nationalization of nationalism lead us to absurdity of our collective identity. Reconstructing Indonesian historiography is an imperative, whithin which local history should have a fair treatment.